2005
DOI: 10.2298/abs0503237j
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the quality of Danube water in the Belgrade region based on benthic animals during periods of high and low water conditions in 2002

Abstract: The present paper states conclusions about the quality of Danube water in the Belgrade Region based on analyses of the invertebrate community. The investigation was performed during periods of high (May, 2002) and low (October, 2002) water conditions. Meio- and macrozoobenthos were observed. Qualitative, quantitative, and saprobiological analy­ses were performed. The sampling area covered five stations along 66 km of the river. The community was represented by 26 species. Aquatic worms were the principal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The Serbian reach of the Danube has been extensively examined since the early sixties (Liepolt 1967; Petrovic 1971Petrovic , 1973Petrovic , 1975Petrovic , 1978Jakovcev 1987Jakovcev , 1988Jankovic & Jovicic 1994;Martinovic-Vitanovic et al 1999;Simic et al 1997;Simic & Simic 2004;Paunovic et al 2005;Jakovcev-Todorovic et al 2005). The results of a 1986 study referring primarily to water pollution problems (Jankovic & Jovicic 1994) showed that water quality in the Serbian reach of the Danube deteriorated compared to the 1960-1970 period.…”
Section: Introductionmentioning
confidence: 99%
“…The Serbian reach of the Danube has been extensively examined since the early sixties (Liepolt 1967; Petrovic 1971Petrovic , 1973Petrovic , 1975Petrovic , 1978Jakovcev 1987Jakovcev , 1988Jankovic & Jovicic 1994;Martinovic-Vitanovic et al 1999;Simic et al 1997;Simic & Simic 2004;Paunovic et al 2005;Jakovcev-Todorovic et al 2005). The results of a 1986 study referring primarily to water pollution problems (Jankovic & Jovicic 1994) showed that water quality in the Serbian reach of the Danube deteriorated compared to the 1960-1970 period.…”
Section: Introductionmentioning
confidence: 99%
“…Fish cover all trophic levels of consumer ecology and provide a powerful tool for assessing aquatic environments (Lin et al, 2021); plankton are an important link in the material and energy transfer of aquatic ecosystems, with phytoplankton playing a vital role in the food chain as the first trophic level (Zhang et al, 2010); zooplankton participate in the material cycle of aquatic ecosystems by feeding on phytoplankton, bacteria and other organisms (Bi et al, 2001;Li et al, 2004); benthic organisms are an essential part of the aquatic food web and provide the bait base for most fish in rivers, and are closely related to the ecological taxa and zonal composition of riverine fish (Šarauskienė et al, 2021); in addition, the species and abundance of microbial communities can reflect changes in aquatic ecosystems. Overall, the aquatic organisms mentioned above can indicate the health of the aquatic environment at a certain level (Xu, 1996;Araújo et al, 2000;Jakovčev-Todorović et al, 2005;Salmaso et al, 2006;Li, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They can also be indicative of a variety of environmental conditions other than pollution. Influence of stream hydrology and physical and chemical factors on aquatic Oligochaeta have been studied by many authors (Elexová 1998;Šporka & Nagy 1998;Moog 2002;Timm et al 2001;Đukić et al 1996;Jakovčev-Todorović et al 2005;Martinovic-Vitanovic et al 2006;Paunovic et al 2003).…”
Section: Introductionmentioning
confidence: 99%